Optimization of stop-hole parameters for cracks at diaphragm-to-rib weld in steel bridges. (November 2019) - Yao, Yue; Ji, Bohai; Fu, Zhongqiu; Zhou, Jian; Wang, Yixun
Abstract: To improve the maintenance effect of stop-hole approach for cracks at diaphragm-to-rib weld, the optimal drilling stop-hole process was investigated by numerical analysis and fatigue tests. Both of the effects of out-of-plane and in-plane deformations on stress characteristics around the stop-hole were analysed. The stress variation influenced by the stop-hole parameters was analysed by finite element analysis. On this basis, relative fatigue tests of nineteen working conditions were conducted to study the cracking characteristics of cracks initiating from the stop-hole. The effects on delaying crack propagation were compared to determine the optimal stop-hole parameters. The results show that drilling a stop-hole could delay crack propagation. There are multiple high stress sub-regions around the stop-hole, which might induce multiple cracks at the stop-hole edge. It is suggested that the stop-hole should be located on the crack extension line, and the edge of the stop-hole intersects exactly with the crack tip with the stop-hole diameter of 24 mm. Highlights: Both of the effects of out-of-plane and in-plane deformations on stress characteristic of stop-hole were analyzed. The multiple stress concentration regions were observed whose effect on multiple cracks was verified in the fatigue test. The reasonable stop-hole position and diameter for diaphragm cracks are suggested.